PEMBUATAN KERAMIK GERABAH BERBASIS LIMBAH PADAT DARI INDUSTRI PULP DAN TANAH LIAT - Sebayang, p.; Ginting, Masno; Henry, - (Teknologi Indonesia, 2010)
The earthenware ceramics have been made based on solid waste from pulp industry (sludge) and clay with various composition (in persentage mass). The preparation of raw materials was done using ball mill for 24 hours until it can pass through 100 mesh shieve. Then those raw materials mixed with 50 ml Polivinylalcohol (PVA), and stirred until homogeneous. The sample was formed using dry pressing with pressure of 25 kgf/cm and dried in a drying oven at 60C for 24 hours. The sintering process using electrical furnace with heating rate of 10C/minute, when, the temperature reaching 900C, it is hold for 2 hours. The optimum composition of earthenware cera mics is 50% solid waste from pulp industry (sludge) and 50% clay with sintering temperature of 900C for 2 hours holding time. At this condition, the properties are: bulk density = 1.37 g/cm, crystal density = 2.71 g/cm, porosity = 39.26 %, and compressive strength = 62.90 kgf/cm2. From the XRD analysis it is shown that there are 5 phases such as: silicon oxide (SiO2), calcite (CaCO3), calsium oxide (CaO), magnesium silicate (MgSiO3) and sillimanete (Al2SiO5). The dominant phase is Calcite (CaCO3) while others are minor phases. From SEM measurement it is shown that the particles of the earthenware ceramic has irregular shape, with particle size less than 5 ?m and pore size less than 1 ?m.